Seminar on Enhancing Students' Interests, Talents, and Creativity at SMA N 2 Lintau Buo - Rudi Pranata; Desmita Desmita; Irda Suryani (Jurnal Masyarakat Religius dan Berwawasan, 2023)
The development of students' talents, interests, and creativity needs to be enhanced at various levels of education. This is done to not only improve school achievements but also to shape students into individuals with integrity, positive attitudes, and strong leadership abilities. In the context of talent and interest development, Community-Based Participatory Research (CBPR) can involve community members in planning and implementing various activities such as seminars, workshops, trainings, exhibitions, or competitions relevant to the interests and talents that are being cultivated.One form of activity that can be undertaken is a seminar focused on boosting students' interests and talents, aiming to motivate them to refine their individual interests and talents. The outcome of such endeavors is that students become capable of identifying their own talents, leading to a greater focus on engaging in extracurricular activities that foster the development of their interests and talents within the school environment.